Effects of Firm Size, Liquidity, Leverage, and Investment Opportunity Set on Earnings Quality - Prety Syahwa Nabilla; Miswaty; Ika Makherta Sutadji (International Journal of Economics, Business and Innovation Research, 2026)
This study investigates the influence of firm size, current ratio, debt-to-equity ratio, and investment opportunity set on the earnings quality of textile and garment manufacturing companies listed on the Indonesia Stock Exchange during the 2021–2025 period. The research is motivated by the unstable performance of Indonesia's textile and garment industry, along with inconsistent findings reported in previous studies regarding the determinants of earnings quality. A quantitative research design was employed using secondary data obtained from audited annual financial statements. The sample consisted of 14 companies selected through purposive sampling, resulting in 70 firm-year observations. The hypotheses were tested using multiple linear regression analysis with IBM SPSS. The empirical findings reveal that firm size, current ratio, and investment opportunity set do not significantly affect earnings quality, whereas the debt-to-equity ratio has a positive and significant effect. These findings provide updated empirical evidence regarding the determinants of earnings quality in Indonesia's textile and garment manufacturing sector and contribute to the development of financial accounting literature, particularly in the context of emerging markets.